El derecho a la Consulta previa a los pueblos indígenas en el Sistema Interamericano de Derechos Humanos. Casos de estudio: Ecuador y Colombia1 (2019)
This article analyzed the contributions of ILO Convention 169 concerning Indigenous and Tribal Peoples in Independent Countries, regarding the right to prior consultation as a tool for the protection of indigenous peoples in the Inter-American Human Rights System. This analysis was based on a qualitative methodology, following the analytical-descriptive approach and using tools such as jurisprudential analysis. The research focused, particularly, on studying the sentence of the Inter-American Court of Human Rights in the case of Sarayaku v. Ecuador. From this sentence, some legal realities can be deduced that foresee the consequences of adopting the prior consultation in the legal systems of Ecuador and Colombia, as well as its impact on the socio-economic reality of those states and their indigenous peoples